Application of the Brainstorming Method to Increase Maharoh Al Kalam in Class XI Science Students at MA Al Karimi : Penerapan Metode Brainstorming untuk Meningkatkan Maharoh Al Kalam pada Siswa Kelas XI IPA di MA Al Karimi - Nurul Badiah; Najih Anwar (Academia Open, 2021)
This research was conducted because researchers found several problems in class XI IPA, namely that the majority of students were less interested in learning Arabic, the purpose of this study was to determine the use of the Brainstorming method to improve maharoh al kalam in class XI IPA students at MA Al Karimi Gresik. . And to find out the increase in maharoh al kalam by applying the Brainstorming method to class XI IPA students at MA Al Karimi Gresik. This research is a classroom action research. The data obtained were collected by means of observation, documentation, and test techniques. The data analysis in this study used a statistical approach and a qualitative approach that used a narrative-qualitative analysis. The results of this study reveal that the Brainstorming method in learning Arabic can improve students' maharoh al kalam based on the data obtained in each cycle.